Ethnic differences in the frequency of β‐amyloid deposition in cognitively normal individuals. (1st February 2022) - Kim, Jaeho; Jung, Sang‐Hyuk; Choe, Yeongsim; Kim, Soyeon; Kim, Beomsu; Kim, Hang‐Rai; Son, Sang Joon; Hong, Chang Hyung; Na, Duk L.; Kim, Hee Jin; Cho, Soo‐Jin; Won, Hong‐Hee; et al.
Abstract: Background: Prevalence estimates of β‐amyloid (Aβ) pathology and their related factors in cognitively normal (CN) individuals are required to better understand the development of Alzheimer's disease (AD) and to facilitate the design of clinical studies. Method: We recruited 448 South Korean CN participants from a Korean tertiary hospital (Samsung Medical Center, SMC) and 323 European CN participants from the US Alzheimer's Disease Neuroimaging Initiative (ADNI) who underwent amyloid PET. We compared the frequencies of Aβ (+) in CN Korean and European participants and investigated which factors explain these differences after conducting genome‐wide association study (GWAS) analysis in each cohort. Result: The frequency of Aβ (+) was higher in the ADNI dataset (32.8%) than in the SMC dataset (18.9%; P <0.001). In particular, the differences between the two groups were prominent in elderly participants ( P = 0.001 for 70–79 years and P = 0.004 for ≥80 years) and homozygous APOE ε3 carriers ( P <0.001). In the SMC GWAS, a locus near the brain‐derived neurotrophic factor gene showed a genome‐wide significant association with Aβ deposition ( P = 3.59 × 10 ‐9 ), while this association was not observed in the ADNI GWAS. The association was also observed in elderly participants ( P <0.001), APOE ε3 homozygote carriers ( P = 0.0024), and another Korean replication set ( P = 0.0056). Furthermore, the interaction between population groups (SMC or ADNI) and rs7481773 was significant ( P = 0.0125). Conclusion: The different frequencies of Aβ (+) between CN Koreans and Europeans might be related to decreased cognitive reserve through their distinct cultural environments or genetic factors.